1977
DOI: 10.1136/hrt.39.10.1128
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of treated acute massive pulmonary embolism.

Abstract: Seventy-two patients surviving initial treatment by pulmonary embolectomy, streptokinase, or heparin for acute massive pulmonary embolism have been reviewed 1 to 9years later. Of these patients, 17 had additional cardiorespiratory disease. There were 12 late deaths (41% of those patients with, and 9% of those patients without additional cardiorespiratory disease). No death was due to chronic pulmonary hypertension, and none to certain recurrence of pulmonary embolism. The causes of death were malignant disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…The in-hospital mortality rate of this patient cohort was 28.6%, which accords with the high mortality rate (18-33%) reported by other investigators, [12][13][14] but is considerably higher than the 8% and 9.5% respective mortality rates of the hemodynamically stable patients included in the Urokinase in Pulmonary Embolism Trial 15 and the Prospective Investigation of Pulmonary Embolism Diagnosis trial. 16 Anticoagulation with heparin was initiated in all 35 patients in the present study and thomboembolytic agents were given to 30 (85.7%).…”
Section: Discussionsupporting
confidence: 76%
“…The in-hospital mortality rate of this patient cohort was 28.6%, which accords with the high mortality rate (18-33%) reported by other investigators, [12][13][14] but is considerably higher than the 8% and 9.5% respective mortality rates of the hemodynamically stable patients included in the Urokinase in Pulmonary Embolism Trial 15 and the Prospective Investigation of Pulmonary Embolism Diagnosis trial. 16 Anticoagulation with heparin was initiated in all 35 patients in the present study and thomboembolytic agents were given to 30 (85.7%).…”
Section: Discussionsupporting
confidence: 76%
“…[12][13][14] The data presented in this report, however, show that post-embolic pulmonary hypertension in patients treated with conventional anticoagulation is not uncommon and that it can be prevented or minimized by initial treatment with thrombolytic agents. The latter, thus, appears to provide an early and sustained benefit for up to 7 years by effecting more complete clot resolution and by preserving the pulmonary vascular response to exercise in the long term.…”
Section: Discussionmentioning
confidence: 69%
“…37 Long-term follow-up studies have consistently demonstrated that incomplete perfusion recovery, even years after acute PE, occurs in one-third to more than two-thirds of patients. [38][39][40][41] Up to 15% of acute PE patients remain symptomatically compromised 2 years after treatment 42 and may have abnormal pulmonary gas exchange (O 2 gradients, dead space, etc) as well. 43 These findings suggest that incomplete clot resolution has clinical manifestations in a significant proportion of acute PE patients, the most severe of which is CTEPH.…”
Section: Discussionmentioning
confidence: 99%